Warrant of Ebenezer Stevens - Stevens, Ebenezer
Warrant signed by Ebenezer Stevens with note by Thomas Packer, a sheriff, relating to the arrest of George Legorse for misconduct in the New Hampshire Provincial Congress.
Speaker of the House of Representatives, New Hampshire Provincial Congress.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Legorse, George; Packer, Thomas, -- active 1746.; New Hampshire. -- Provincial Congress; Arrest -- New Hampshire; New Hampshire -- History -- Colonial period, ca. 1600-1775.; Public officials